Piezotronics-enabled performance enhancement in ZnONR/n-MoS2/i-MoS2/p-Si photovoltaics - Rathnakannan, K.; Parasuraman, R. (Journal of computational electronics, 2025)
This study explores the impact of the piezotronic effect on the performance of a ZnO nanorod/n-MoS 2 /i-MoS 2 /p-Si photovoltaic nano-heterostructure for achieving high-efficiency energy harvesting. We aimed to optimize the thickness of each layer in the piezo-photoelectric physical model to improve the J–V characteristics and energy band alignment. We found that a thickness of 5 nm for n-MoS 2 and 100 nm for ZnO NR, and the doping concentration led to the highest photoconversion efficiency of 28.08%. This configuration generated piezocharges at the ZnO/MoS 2 interfaces under applied strain ranging from − 1% to 1. This structure has potential for developing high-efficiency solar cells.